A snapshot of Bulgarian school teachers' familiarity with, use of, and opinions on artificial intelligence at the threshold of its incorporation into the educational process - Denitza Anguelova Kurshumova (Springer, 2024)
Abstract The current study was designed within a survey-based quantitative research methodology in order to investigate Bulgarian teachers' familiarity with, use of, and attitudes toward artificial intelligence (AI) at the nascent stage of its integration into the Bulgarian education system. The survey was completed by 2252 teachers, of whom 16.30% were men and 83.70% were women. The majority of the teachers (72%) reported some level of familiarity with AI technology. Higher levels of familiarity were significantly associated with younger teachers (aged 20 to 29), mathematics, sciences, and technology subject areas, as well as the male gender. More than 50% of the teachers reported using AI technology in their instruction. Familiarity with AI technology was the only significant predictor of AI use, overriding the effect of other variables. The teachers used AI technology to prepare teaching, assessment, and homework materials; design individual and team tasks; and grade students' work. The teachers who regularly used AI technology were more favorable towards AI in contrast to those who seldom or never employed AI. The majority of the respondents recognized the need for teacher training in AI technology and expressed willingness to participate in teacher training initiatives. Therefore, the current situation requires teacher education programs to harness teachers' needs by equipping them with relevant AI literacy and skills that they could apply to the critical adoption of suitable AI tools. Educational institutions and stakeholders should provide guidelines and consultancy regarding technical, methodological, and ethical issues concerning the instructional use of AI technology.